2021
DOI: 10.1038/s41598-021-86777-z
|View full text |Cite
|
Sign up to set email alerts
|

Preseismic atmospheric radon anomaly associated with 2018 Northern Osaka earthquake

Abstract: Despite the challenges in identifying earthquake precursors in intraplate (inland) earthquakes, various hydrological and geochemical measurements have been conducted to establish a possible link to seismic activities. Anomalous increases in radon (222Rn) concentration in soil, groundwater, and atmosphere have been reported prior to large earthquakes. Although the radon concentration in the atmosphere is lower than that in groundwater and soils, a recent statistical analysis has suggested that the average atmos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…Authors like Omori et al [47], Schekotov et al [48] and Mohammad et al [49] fails to correlate radon anomaly with parameters like tidal loading and atmospheric electromagnetic radiation before earthquakes. Quiescence in radon concentration was also observed by Muto et al [50] before the 2018 Osaka earthquake. A positive correlation between radon anomaly and earthquakes was also recently reported by some authors [51][52][53], where analytical methods like chaos method, decomposition methods, machine intelligence and stacking methods were successfully used to identify the radon anomaly.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Authors like Omori et al [47], Schekotov et al [48] and Mohammad et al [49] fails to correlate radon anomaly with parameters like tidal loading and atmospheric electromagnetic radiation before earthquakes. Quiescence in radon concentration was also observed by Muto et al [50] before the 2018 Osaka earthquake. A positive correlation between radon anomaly and earthquakes was also recently reported by some authors [51][52][53], where analytical methods like chaos method, decomposition methods, machine intelligence and stacking methods were successfully used to identify the radon anomaly.…”
Section: Introductionsupporting
confidence: 63%
“…This observation ignites opti-mism among researchers to predict earthquakes by monitoring radon anomaly and soon it becomes a global phenomenon that continues till dates [5-11, 37-39, 47-53]. Uncertainty and inaccuracy in prediction remained the main issue of present-day researchers, which is very well visible from some recent reports [37][38][39][47][48][49][50][51][52][53]. Chowdhury et al [38] and Sahoo et al [39] from the east and north India, respectively observed unpredicted earthquakes and false radon anomaly peaks, though they observed a positive correlation between them.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, continuous monitoring of soil gas radon and water radon concentrations along with the Amritsar (Punjab, India) seismic zone correlation showed that the amplitude of radon gas anomalies was positively correlated with earthquake magnitude [57]. In addition, recent studies revealed a significant decrease in radon concentration within continuous measurements of radon concentration in the atmosphere before the 2018 earthquake in northern Osaka, Japan [58] and peculiar changes in radon concentration in the atmosphere two months before the 1995 Kobe earthquake in Japan [59]; Fu et al [60] studied the radon gas anomalies in northern and northeastern Taiwan before the earthquake and observed a significant increase in soil radon concentration from a few days to a few weeks before the earthquake. Finally, it is reasonable that the amount of emitted radon could depend on the rupture length of the fault, that is, the magnitude of the seismic event.…”
Section: Discussionmentioning
confidence: 99%
“…The 2012 Pollino (Calabria, Italy) seismic sequence, culminating in a moment magnitude (Mw) 5.2 earthquake on 25 October 2012, was investigated by exploiting data collected during a long-term continuous radon monitoring experiment performed in the epicentral area from late 2011 to the end of 2014, this work has identified characteristic variations in radon exhalations during the preparation processes of large earthquakes [57]. The necessity of continuous monitoring of atmospheric radon concentrations combined with statistical anomaly detection methods to evaluate future seismic risks [45,52,[58][59][60], as well as low-cost radon monitoring methods and the application of expert systems to the prevention of indoor radon gas exposition risks, have been reported [61][62][63][64].…”
Section: Earthquakes and Radonmentioning
confidence: 99%
“…During this seismic quiescence, deep-seated sedimentary layers in the Osaka Basin, which might have been the main sources of radon, became less damaged and fractured. The reduction in damage led to a decrease in radon exhalation to the atmosphere near the fault, causing the pre-seismic radon decrease observed in the atmosphere [60].…”
Section: Radon and Earthquakesmentioning
confidence: 99%